Do patient-reported outcomes and experiences differ among patient groups accessing community mental health services? Interrogating DIALOG data through the equity lens - Rahul Bhattacharya; Stuart G. Spicer; Akshith Shetty; Katelyn Smalley; Paul Sharpe; Richard Byng (BJPsych Bulletin, 2026)
Aims and method We aimed to compare differences in DIALOG scale patient-reported experience measures and patient-reported outcome measures scores between different patient groups accessing adult mental health services. Pooled anonymised data of 11 198 DIALOG scores from 5007 unique patients were disaggregated (based on age, gender, ethnicity and socioeconomic deprivation) and analysed. We compared statistical differences between groups in their means scores, and carried out regression analysis converting data to a binomial for satisfaction to control for variables. Results Asian and Black patients had greater levels of satisfaction across several domains compared with White British patients. Women, younger patients and those living in more deprived areas had poorer levels of satisfaction. Clinical implications Disaggregated large routinely collected outcome data can offer useful intelligence on monitoring of health inequity. Overall health inequity assessment needs a nuanced interpretation and triangulation of outcome data with access experience, including coercion and physical health.